If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3p + 4 = -9(5p + -10) + -2(-5 + -5p) Reorder the terms: 4 + -3p = -9(5p + -10) + -2(-5 + -5p) Reorder the terms: 4 + -3p = -9(-10 + 5p) + -2(-5 + -5p) 4 + -3p = (-10 * -9 + 5p * -9) + -2(-5 + -5p) 4 + -3p = (90 + -45p) + -2(-5 + -5p) 4 + -3p = 90 + -45p + (-5 * -2 + -5p * -2) 4 + -3p = 90 + -45p + (10 + 10p) Reorder the terms: 4 + -3p = 90 + 10 + -45p + 10p Combine like terms: 90 + 10 = 100 4 + -3p = 100 + -45p + 10p Combine like terms: -45p + 10p = -35p 4 + -3p = 100 + -35p Solving 4 + -3p = 100 + -35p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '35p' to each side of the equation. 4 + -3p + 35p = 100 + -35p + 35p Combine like terms: -3p + 35p = 32p 4 + 32p = 100 + -35p + 35p Combine like terms: -35p + 35p = 0 4 + 32p = 100 + 0 4 + 32p = 100 Add '-4' to each side of the equation. 4 + -4 + 32p = 100 + -4 Combine like terms: 4 + -4 = 0 0 + 32p = 100 + -4 32p = 100 + -4 Combine like terms: 100 + -4 = 96 32p = 96 Divide each side by '32'. p = 3 Simplifying p = 3
| 1/8(a+3)=1/4(9-a) | | (n+3)5=3(2n-1) | | 6x6/7 | | 2/3G=-5/2 | | (6/x-4)/(2x-3)=0 | | 10y-6=4y+8 | | 8h=26 | | 7-(2z-5)=6-3z | | 2/3y+v=x | | v-9=214 | | 16+8x=25+15+3 | | -13x-13=2x-46 | | 220=4(-2+7x)+4 | | y=2/3(7)+4 | | -8(1+7m)=384 | | 0=4(4t^2+16t-7) | | 3.50+2.50x=25 | | -15+m/4=-11 | | -11n+16=-10n-5 | | -4(2-c)=12 | | -3(4r+-8)=-36 | | 49/98=a/112 | | 2/5+4/7 | | y=2/3(5)+4 | | 13.95x+1.95=85.95 | | (-2/x-3)+(3/x+3)=(-12/x^2-9) | | -7-y-y=-1 | | Ab+3c=2 | | r-5.20=3.50 | | 0.3(x+80)+1.5x=105 | | n/3-10=-6 | | y=(c-d)x+6 |